THE SPECIFIC COMPETENCE OF ADMINISTRATIVE WORK AS THE MAIN OBJECT OF CERTIFICATION - A. Medvedev (Вестник университета)
The article investigates administrative work in comparison with other forms and types of labor of members of the organization. The functional purpose of managerial work, as well as its features, is considered. The issue of managerial personnel potential is touched upon